2018
DOI: 10.21608/ejdr.2019.12939.1028
|View full text |Cite
|
Sign up to set email alerts
|

Surveys of Wild Vertebrates in the Kharga and Dakhla Oasis and Their Impact on the New Reclamation Areas in Egypt

Abstract: Kharga and Dakhla Oases were carried out during 2014-2018, inclusive. Thirty-five common species were recorded. There was one reptile, the Horned Viper. There were twenty-two birds representing twelve orders: eight are common resident species, and the rest are migrants. There were twelve mammals, including two carnivores, eight rodents and two bats. Regular surveys of vertebrates are needed to evaluate the effect of human activities in the new reclamation areas, and to update different lists of reptiles, birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…The numbers of bird species recorded in this study were 16 species, theses in line with Mohallal and Ahmed (2018) who reported 22 bird species at Kharga and Dakhla Oases in the New Valley Governorate in the south of the western desert of Egypt. In contrast, it is less than the recorded (83 bird species) by White et al, (2013) at Bahariya Oasis, Western desert, Egypt.…”
Section: Discussionsupporting
confidence: 91%
“…The numbers of bird species recorded in this study were 16 species, theses in line with Mohallal and Ahmed (2018) who reported 22 bird species at Kharga and Dakhla Oases in the New Valley Governorate in the south of the western desert of Egypt. In contrast, it is less than the recorded (83 bird species) by White et al, (2013) at Bahariya Oasis, Western desert, Egypt.…”
Section: Discussionsupporting
confidence: 91%
“…Diversity and abundance of migratory waterbird communities in natural and artificial agricultural wastewater habitats of New Valley Governorate, Egypt orders were abundant in species, others, such as Suliformes and Coraciiformes, had a limited representation, each consisting of only one species. Several research studies conducted on bird surveys in the New Valley region support the current results (Goodman et al, 1986;Churcher et al, 2008;Ibrahim, 2011;Mohallal & Ahmed, 2018). Numerous researchers found that the artificial wetlands are effective and important habitats for waterbirds throughout different seasons, including wintering and migrating (Paracuellos & Telleria 2004;Rendon et al, 2008;Sebastián-González et al, 2010;Pérez-García et al, 2014;Pandiyan & Nagarajan 2014).…”
supporting
confidence: 61%
“…This study is aimed at filling knowledge gaps by monitoring the spatial shifts of habitat use by water birds in a wetland complex, in the New Valley region that is located on the southern part of the Western Desert of Egypt. This area, comprising those oases like Dakhla and Kharga, depends mainly on agriculture that gives rise to significant drainage of water and sewage from the groundwater (Mohallal & Ahmed 2018;Elbeih & Zaghloul 2021;Darwish 2020). Also, this research involves extensive field surveys and analysis to show how the artificial wetlands are supporting waterbird populations and ascertaining their possible role in conservation efforts, in the face of environmental challenges.…”
Section: Introductionmentioning
confidence: 99%